Quantitative analysis of change in bone volume 5 years after sinus floor elevation using plate-shaped bone substitutes: a prospective observational study - Takafuji, Kyoko; Oyamada, Yutaro; Hatakeyama, Wataru; Kihara, Hidemichi; Shimazaki, Nobuko; Fukutoku, Akihiro; Satoh, Hiroaki; Kondo, Hisatomo (International journal of implant dentistry, 2024)
Purpose Tricalcium phosphate (TCP) has osteoconductive ability and reportedly offers similar clinical results as autogenous bone grafts in dental implant treatment. However, few reports quantify temporal changes in augmented bone volume after sinus augmentation. We aimed to establish a three-dimensional (3D) quantification method to assess bone volume after sinus augmentation and to evaluate biocompatibility of the TCP plate. Methods Maxillary sinus floor augmentation was performed employing the lateral window technique, and plate-shaped β-TCP (TCP plate) was used instead of granular bone grafting materials. After lifting the sinus membrane, the TCP plate was inserted and supported by dental implants or micro-screws. The changes in bone volumes in the maxillary sinus before and after surgery were recorded using cone-beam computed tomography, saved as Digital Imaging and Communications in Medicine-formatted files, and transformed to Standard Triangle Language (STL)-formatted files. Pre- and post-operative STL data of bone volume were superimposed, and the augmented bone volume was calculated. Moreover, changes in bone volumes, TCP plate resorption rates, and bone heights surrounding the implants were three dimensionally quantified. Results Fifteen implants in nine subjects were included in this study. TCP plates secured long-term space making, with results similar to those of granular bone substitutes. Newly formed bone was identified around the implant without bone graft material. TCP plate was absorbed and gradually disappeared. Conclusions A novel 3D quantification method was established to evaluate changes in bone volume. Clinical application of TCP plate in sinus augmentation could be a better procedure in terms of prognosis and safety.